Effect of cassava legumes intercropping on yield and yield components of compound crops in Jinka on station, Southern Ethiopia - Gezahegn, Biruk; Tadesse, Awoke; Tadesse, Anteneh; Kelifa, Zeynu (International Journal of Agricultural Research, Innovation and Technology, 2022)
A field experiment was carried out during the 2017-18 cropping season at Jinka Agricultural Research Center on station, South Omo zone, Southern Ethiopia, to determine suitable legumes in cassava legume intercropping on yield and land use efficiency of both crops. The experiment consisted of 7 treatments (cassava with haricot bean, cowpea, and pigeon pea as intercrop compared with cassava, haricot bean, cowpea and pigeon pea as sole) laid in RCBD in three replications. Statistical analysis showed that, intercropping cassava with haricot bean, cowpea and pigeon pea resulted in 54, 56 and 21% greater land use efficiency than for either crop grown alone. The highest MAI was obtained by growing cassava with haricot bean (18310.8) followed by cassava with cowpea (14524.4) whereas relatively the lowest was cassava with pigeon pea (6005.6). Based on the present finding, intercropping of cassava with haricot bean had more economic advantage (52219.8 Ebirr) than the other crop combination or grown alone. Therefore, intercropping cassava with grain legumes such as haricot bean and cowpea is important to cassava farmers since it would provide additional crop yield during the early cassava growth stage with the same piece of land and more profitable related to cost benefit. Therefore, use of cassava intercropping with haricot bean can be recommended for cassava producing farmers at Jinka and its vicinity. Int. J. Agril. Res. Innov. Tech. 12(1): 30-33, June 2022